Development of Public Relations Media for Tourism in Phetchaburi Province with Augmented Reality Technology - Keowsawat, Paniti (DEC Journal : Art and Design, 2022)
The purposes of the research were 1) to develop the public relations media for tourism in Phetchaburi province with augmented technology and 2) to evaluate the user’s satisfaction and acceptance level on the public relations media. The population was the tourists who visited Phetchaburi province and the sample group comprised 200 tourists chosen by simple random sampling. The research tools were 1) public relations media for tourism in Phetchaburi province application 2) Phetchaburi provincial slogan postcard 3) the user’s satisfaction evaluation form on the public relations media. The statistics used in the research were average and standard deviation. After the public relations media had been developed, the result revealed that 1) public relations media for tourism in Phetchaburi province application was at the high level, the average of 4.38 and the standard deviation of 0.57. 2) Phetchaburi provincial slogan postcard was at the high level, the average of 4.33 and the standard deviation of 0.59 3) the knowledge contribution and usage were at the high level, the average of 4.35 and standard deviation 0.53. The overall result was the high level, the average of 4.36 and the standard deviation of 0.56.